Ultrasound-augmented anti-inflammatory exosomes for targeted therapy in rheumatoid arthritis. Issue 38 (7th September 2022) - Tang, Yuanjiao; Wu, Zihe; Guo, Ruiqian; Huang, Jianbo; Rong, Xiao; Zhu, Bihui; Wang, Liyun; Ma, Lang; Cheng, Chong; Qiu, Li
Abstract : A novel kind of inherent anti-inflammatory exosome (AI-Exo) was prepared via integrating RAW264.7 macrophage-derived exosomes and interleukin-10 by an electroporation method, which is used for ultrasound-augmented therapy. Abstract : Rheumatoid arthritis (RA), one of the systemic autoimmune diseases, features dysregulated inflammation that can eventually lead to multi-joint destruction and deformity. Although current clinical RA treatment agents including non-steroidal anti-inflammatory drugs, disease-modifying antirheumatic drugs, and biological agents can alleviate symptoms, there can be long-term drug dependence and considerable side effects. To promote the course of RA from inflammation to resolution and ultimately terminate the vicious cycle of recrudescence, it is important to regulate the pro-/anti-inflammatory abilities of macrophages for constructing an immunosuppressive or anti-inflammatory microenvironment. Macrophage-derived exosomes can be homed or targeted to inflammatory tissues or cells; however, the insufficient anti-inflammatory abilities and intrinsic off-target effects of these exosomes often result in unsatisfactory treatment effects, which remains a challenge in the treatment of RA. Here, we proposed a novel kind of inherent anti-inflammatory exosome (AI-Exo), which was prepared via integrating RAW264.7 macrophage-derived exosomes and a powerful anti-inflammatory immune modulator interleukin-10 by an electroporation method. Then, non-invasive ultrasound was used to increase the permeability of blood vessels and augment the targeted accumulation of AI-Exo to inflammatory tissues, which could promote macrophage polarization to M2 phenotypes, relieve inflammation symptoms, stimulate resolution, and accelerate tissue repair against collagen-induced arthritis. This work intensely supports that ultrasound-augmented AI-Exo has significant targeted anti-inflammatory therapeutic effects, and the combined mechanism of anti-inflammation and pro-resolution gives unique insights into the treatment of not only RA but also other inflammatory diseases, which provides an effective strategy and a promising prospect for future wider biomedical applications and clinical transformations.